Sex-specific familial clustering of myocardial infarction in patients with acute coronary syndromes. - Banerjee, A; Silver, L; Heneghan, C; Welch, S; Bull, L; Mehta, Z; Banning, A; Rothwell, P (2009)
BACKGROUND: Family history of premature myocardial infarction (MI) in first-degree relatives is a risk factor for MI and an indication for primary prevention. Although excess mother-to-daughter "transmission" occurs in ischemic stroke, no published studies have considered sex-of-parent/sex-of-proband interactions in the heritability of MI. METHODS AND RESULTS: In a population-based study (Oxford Vascular Study) of all patients with acute coronary syndromes (ACS), irrespective of age, family history of all acute vascular events and related risk factors were analyzed by sex and age of both probands and first-degree relatives. Premature events were categorized as occurring at age <65 years. Of 835 probands with 1 or more ACS, 623 (420 men) had incident events and complete family history data. In probands with premature ACS, maternal history of both MI and of all vascular events were more common in female than male probands (odds ratio [OR], 2.25; 95% CI, 1.02 to 4.94; P=0.04 and OR, 3.03; 95% CI, 1.47 to 6.26; P=0.002, respectively). No such effect existed for paternal history (OR, 1.00; 95% CI, 0.46 to 2.10; P=0.99 and OR, 1.19; 95% CI, 0.58 to 2.43; P=0.63, respectively). Age at ACS in probands was highly correlated with age at MI in mothers (r=0.46, P<0.001), regardless of the proband's sex. Consequently, history of premature maternal MI was strongly associated with premature ACS and premature MI in female (OR, 10.52; 95% CI, 2.17 to 56.6; P=0.001 and OR, 7.31; 95% CI, 1.55 to 34.6; P=0.004, respectively) and male probands (OR, 3.88; 95% CI, 1.20 to 12.6; P=0.01 and OR, 3.63; 95% CI, 1.13 to 11.60; P=0.02, respectively). CONCLUSIONS: Important sex-of-parent/sex-of-proband interactions exist in the family history of MI in patients with ACS. Greater emphasis should be placed on maternal than paternal history of MI, particularly in women aged <65 years.